2019
DOI: 10.1111/bju.14781
|View full text |Cite
|
Sign up to set email alerts
|

Value of supranormal function on 99mTc‐mercaptoacetyltriglycine renal scan in paediatric patients with obstructive hydronephrosis

Abstract: Objectives To study related factors and clinical significance of supranormal function in paediatric patients with pelvi‐ureteric junction obstruction, and to predict which factors cause renal function overestimation. Patients and Methods Patients who underwent pyeloplasty from 2012 to 2017 were prospectively collected. Variables were compared between patients with and without supranormal function on 99mTc‐mercaptoacetyltriglycine renal scan (supranormal defined as differential renal function [DRF] ≥55%). Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Nonetheless, it should be noted that the hydronephrotic kidney may present with a relatively higher function than the normal contralateral one, known as supernormal function phenomena; several theories have been proposed to explain such phenomena, including true compensatory hyperfunction or a technical artifact [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it should be noted that the hydronephrotic kidney may present with a relatively higher function than the normal contralateral one, known as supernormal function phenomena; several theories have been proposed to explain such phenomena, including true compensatory hyperfunction or a technical artifact [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a supranormal function in our present study is 3.6%, which is lower than the previous reports in pediatric age groups which ranged from 9% to 21%. [ 3 4 7 10 12 ] This lower incidence may be attributed to the late diagnosis of UPJO at adulthood which affect the renal function of the affected kidney at the first presentation. Concerning renal function outcome after pyeloplasty, it was documented that children with snDRF who underwent pyeloplasty were found to have an obvious decrease in hydronephrosis, and 70% of them had a decrease in postoperative DRF, reaching a normal level of function (40%–55%).…”
Section: Discussionmentioning
confidence: 99%
“…In a pediatric cohort, it has been shown that renal function could decrease in patients with snDRF and increased APD of the renal pelvis preoperatively when hydronephrosis improved after surgery. [ 12 ] They recommended close surveillance and early surgical treatment in those children if hydronephrosis or drainage time on renogram deteriorated. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations